Dermatofunctional physiotherapeutic intervention in female patients with 3rd degree burns (Research, Society and Development, 2025)
Third-degree burns represent highly complex injuries, characterized by the complete destruction of skin layers and, often, the involvement of underlying structures. In women, such injuries lead to functional, aesthetic, and psychosocial repercussions, directly impacting self-esteem, body image, and social reintegration. The objective of this study is to analyze the importance of dermatofunctional physiotherapy in the rehabilitation of women affected by third-degree burns, highlighting functional, aesthetic, and psychosocial benefits. This bibliographic study, with a qualitative approach, analyzed publications indexed in national and international scientific databases between 2004 and 2025, focusing on physiotherapeutic management of severe burns in female patients. The results show that resources such as electrotherapy, photobiomodulation, radiofrequency, cryotherapy, lymphatic drainage, and compression therapy contribute to scar modulation, prevention of contractures, improvement of joint mobility, and reduction of pain. In addition to physical benefits, the relevance of a humanized and empathetic approach stands out, promoting emotional reconstruction and acceptance of bodily scars. Multiprofessional integration involving physiotherapists, psychologists, physicians, and occupational therapists enhances outcomes and ensures comprehensive care. It is concluded that dermatofunctional physiotherapy is essential in the rehabilitation of women affected by third-degree burns, promoting functional and aesthetic improvements, as well as contributing to the recovery of self-esteem and quality of life.